2012
DOI: 10.1177/0961203312441048
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean fever gene (MEFV) mutations as a modifier of systemic lupus erythematosus

Abstract: The objective of this study was to assess the prevalence of the Mediterranean FeVer (MEFV) gene mutations in systemic lupus erythematosus (SLE) patients and their effect on organ involvement, as well as disease activity and severity. The frequencies of three familial Mediterranean fever-related MEFV gene mutations (M694V, V726A and E148Q) were investigated in 70 SLE patients. Organ involvement, Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) damage index and Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…However, the modifying role of M694V mutation on the clinical manifestation of SLE is not supported by our results. This finding is in contrast to the study by Shinar et al (29). It may be explained by different frequency of alleles and genotypes and different penetration between populations.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the modifying role of M694V mutation on the clinical manifestation of SLE is not supported by our results. This finding is in contrast to the study by Shinar et al (29). It may be explained by different frequency of alleles and genotypes and different penetration between populations.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent study, it was shown that MEFV mutation carriage contributes to an excess of inflammatory manifestations such as fever and pleuritis while protecting from more severe renal involvement. 9 In conclusion, FMF and SLE can rarely be seen together. Presence of MEFV mutation in SLE may modify disease phenotype as enhanced inflammatory episodes and attenuated renal manifestations.…”
Section: Discussionmentioning
confidence: 91%
“…20 Fever and serosal involvement in FMF usually subside within 1-3 d while they are more prolonged in SLE. 9 These common findings may cause difficulties in differential diagnosis of two diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLE, which is characterized primarily by overactivation of the adaptive immune system, is a good example to understand this interrelation. It is thought that FMF or the presence of MEFV gene mutations confer some protection from SLE and the two diseases rarely overlap (49), but in the case of their presence, MEFV mutations are still associated with higher disease activity indices and early onset disease (23), and exon 10 mutations with more severe disease and nephritis in patients with SLE (24). Thus, MEFV variants may potentially modify the course of glomerulonephritides not primarily mediated by IL-1β and the innate immune system like membranous nephropathy, immunoglobulin A nephropathy, and lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%